2018
DOI: 10.18632/oncotarget.26260
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiling identifies novel NTRK fusions in neuroendocrine tumors

Abstract: CGP results from >60,000 cases were screened to identify NTRK fusion events from cases of neuroendocrine tumors. 2417 NET patients from diverse anatomic sites were identified. From this dataset, six cases harbored NTRK fusions which included intra- and inter-chromosomal translocations. A NTRK fusion frequency of approximately 0.3% was found across all subtypes of NETs. Three cases involved translocations of NTRK1 with unique fusion partners (GPATCH4, PIP5K1A, CCDC19). Co-occurring alterations occurred in five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 17 publications
(14 reference statements)
2
34
0
1
Order By: Relevance
“…However, DNA and RNA sequencing of the two first patients demonstrate the introduction of premature stop codons by these fusions and a lack of transcription (Figure ), which is tantamount to a loss‐of‐function of the chimeric proteins due to the absence of tyrosine kinase domains. Frameshifts in NTRK fusion transcripts have been reported in only a single case of a primary undifferentiated neuroendocrine carcinoma so far . Finally, the third case exemplifies a recombined transcript whose functionality cannot be assessed by our analysis, although the absence of both an endogenous start codon and detectable RNA makes subsequent translation highly unlikely.…”
Section: Discussionmentioning
confidence: 80%
“…However, DNA and RNA sequencing of the two first patients demonstrate the introduction of premature stop codons by these fusions and a lack of transcription (Figure ), which is tantamount to a loss‐of‐function of the chimeric proteins due to the absence of tyrosine kinase domains. Frameshifts in NTRK fusion transcripts have been reported in only a single case of a primary undifferentiated neuroendocrine carcinoma so far . Finally, the third case exemplifies a recombined transcript whose functionality cannot be assessed by our analysis, although the absence of both an endogenous start codon and detectable RNA makes subsequent translation highly unlikely.…”
Section: Discussionmentioning
confidence: 80%
“…A recent study investigating the contribution of NTRK fusions in neuroendocrine tumors reported six cases, originating from various anatomic sites that include the pancreas, uterus, and lung [68]. Interestingly, in three patients, the NTRK fragment was 5′ to its fusion partner.…”
Section: Ntrk Oncofusionsmentioning
confidence: 98%
“…Surprisingly, this patient also had a cooccurring KRAS Q61P mutation. The presence of cooccurring mutations with driver tyrosine kinase alterations has been rarely reported [67,68]. Nonetheless, this scenario warrants that cooccurring mutations with NTRK alterations should be considered as they may pose a resistance liability and limit durability of the response.…”
Section: Ntrk Oncofusionsmentioning
confidence: 99%
“… 1 ∗ Gene nomenclature and chromosomal localizations are described according to the Human Genome Nomenclature Committee database; 5′ fusion partners associated with more than one NTRK gene are in bold; fusions in which the NTRK gene is listed as the 5′ partner are not included. 39 † A brief history of NTRK fusions ( http://ntrkfusions.com/a-brief-history-of-ntrk-fusions , last accessed February 5, 2019). ‡ Loxo Oncology, Inc., data on file.…”
Section: Ntrk Genes In Cancermentioning
confidence: 99%